Galilean Podolsky electrodynamics - Pompeia, P. J. [UNESP]; De Montigny, M.; Khanna, F. C. (World Scientific Publishing, 2009)
We analyze non-rclativistic Limits of Podolsky generalized electrodynamics in the context of the 5-dimensional Galilean formalism. The 'electric' and 'magnetic' limits are studied in analogy with the work of Le Bellac and Levy-Leblond (1973). © 2009 World Scientific Publishing Co. Pte. Ltd.